Virally mediated expression of a biologically active peptide to restrain the nuclear functions of ERK1/2 attenuates learning extinction but not acquisition - Bar Izkovich; Adonis Yiannakas; Sapir Ne’eman; Sailendrakumar Kolatt Chandran; Kobi Rosenblum; Efrat Edry (Molecular Brain)
Abstract Peptide drug technologies offer powerful approaches to develop potent and selective lead molecules for therapeutic and research applications. However, new and optimized delivery approaches are necessary to overcome current pitfalls including fast degradation in cells and tissue. Extracellular signal-regulated kinases 1/2 (ERK1/2) exemplifies proteins that play crucial and varied roles within distinct cellular compartments. Here, we established an innovative method, based on viral vectors, which utilizes the endogenous biogenesis of neurotrophins to deliver and express a biologically active peptide to attenuate specifically ERK1/2 nuclear functions in specific brain area of the adult forebrain. In contrast to our hypothesis, nuclear functions of ERK1/2 in the forebrain are fundamental for the extinction of associative-aversive memories, but not for acquisition, nor for retrieval of these memories. Our research demonstrates the feasibility and applicability of viral vectors to deliver a peptide of interest to manipulate specific molecular processes and/or protein interactions in specific tissue.